A Study of SuperDARN Response to Co‐occurring Space Weather Phenomena. Issue 9 (2nd September 2019) - Chakraborty, S.; Baker, J. B. H.; Ruohoniemi, J. M.; Kunduri, B.; Nishitani, N.; Shepherd, S. G.
Abstract: The Sun was remarkably active during the first week of September 2017 producing numerous solar flares, solar radiation storms, and coronal mass ejections. This activity caused disruption to terrestrial high‐frequency (HF, 3–30 MHz) radio communication channels including observations with the Super Dual Auroral Radar Network (SuperDARN) HF radars. In this paper, we analyze the response of SuperDARN groundscatter observations and decreases in background sky noise level in response to multiple solar flares occurring in quick succession and co‐occurring with solar energetic protons and auroral activity. We estimate the attenuation in HF signal strength using an approach similar to riometry and find that the radars exhibit a nonlinear response to compound solar flare events. Additionally, we find that the three different space weather drivers have varying degrees of influence on the HF signal properties at different latitudes. Our study demonstrates that in addition to monitoring high‐latitude convection, SuperDARN observations can be used to study the spatiotemporal evolution of disruption to HF communication during extreme space weather conditions. Key Points: SuperDARN HF radars observed a drop in signal strength in response to extreme space weather phenomena during September 2017 Multiple solar flares occurring in quick succession produce nonlinear effects on radio wave absorption Co‐occurring space weather phenomena have varying degrees of impact at different latitudes Plain Language Summary: High‐frequency (HF, 3–30 MHz) communication system plays an essential role in emergency communications such as amateur radio, missile defense, and air traffic control. Most of these systems solely depend on HF communication that can travel beyond the horizon (over the horizon) without any relay or repeater network. This bending of the HF signal is feasible because of the presence of an electrically charged upper atmosphere, also known as ionosphere which can bend the HF signal back to the Earth. This electrically conducting upper atmosphere (ionosphere) can be influenced by the Sun and the outer space, commonly known as space weather. Extreme space weather events such as solar flares, radiation storms, and geomagnetic storms produced by the Sun can alter the state of the ionosphere and disrupt HF communication. During the first week of September 2017, the Sun produced numerous solar flares, radiation storms, and geomagnetic storms. This paper compares the impacts of isolated versus co‐occurring space weather disturbances on HF communications as observed by the Super Dual Auroral Radar Network HF radar network distributed across the North American sector.